Technetium scintigraphy as a predictive tool of thyroid malignancy - Mohanty, Sanjeev; ., Sreenivas; T., Vinay Raj; ., Devipriya; M., Vinoth (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Thyromegaly is a common cause of physician consultation. Solitary thyroid nodules are conventionally viewed with suspicion. Clinical examination cannot reliably distinguish between a solitary thyroid nodule and a dominant nodule in multinodular goiter. Ultrasonographical examination has its own pitfalls. Technetium 99 is a commonly used modality for the functional assessment of solitary thyroid nodule detection. It has the advantage of low cost with lower radiation dose to the exposed patients. On literature search, studies on technetium 99 scintigraphy for thyroid in context to the Indian scenario do not yield much information and very few studies are notable. This study was conducted to correlate and qualify thyroid cold nodule as detected by Technetium 99 pertechnetate thyroid scan. This study was conducted to correlate, qualify and compare the predictive value of Technetium 99 pertechnetate scintigraphy on solitary thyroid nodule via fine needle aspiration cytology and to countercheck with histopathological examination. Methods: A prospective cohort study in a NABH, NAAC and JCI accredited tertiary care teaching university hospital was conducted over a period of 36 months. All the subjects underwent clinical assessment of the neck included standard examination techniques to segregate solitary thyroid nodules. They were then subjected to Technetium 99 pertechnate scintigraphy using the standard protocol. All the patients with solitary cold nodule underwent FNAC followed by nodule excision or hemi-thyroidectomy under general anaesthesia. All the specimens underwent histo-pathological examination by an experienced histopathologist. The results were statistically analysed using pearson chi-square test. Results: Cold nodules as detected by Technetium 99 pertechnetate thyroid scan is a reasonable indicator of probable malignancy via fine needle aspiration cytology. Occurrence of cold nodules is highest in 3rd to 5th decade of life (21-50 year age group). Occurrence of cold nodules is higher in females (83%) whereas occurrence of malignancy in cold nodules is higher in males (85%). Occurrence of malignancy in cold nodules is higher in subjects less than 21 and above 50 years. Conclusions: Technetium 99m pertechnetate thyroid scintigraphy is an important preoperative tool in management of thyroid nodules and its routine use in all such patients is recommended especially to rule out cold nodules.